2011
DOI: 10.1007/s00264-011-1411-7
|View full text |Cite
|
Sign up to set email alerts
|

The sex specificity of hip-joint muscles offers an explanation for better results in men after total hip arthroplasty

Abstract: The equal relative muscle distribution in men and women around the hip joint reflects neither sex-related differences observed in clinical outcomes after THA nor bony anatomy. Yet men exhibited more muscle reserves (muscle volume; absolute and in relation to body mass) , which could explain the better outcome in men after THA. Furthermore, this suggests the extraordinary importance of muscle-sparing surgical approaches in women. The results represent the rationale for designing and analysing future studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…The purposes of our study were to evaluate the effect of hip abductor muscle strength on hip function, to validate the utility of our CT-based analysis for the quantification of muscle volume and muscle degeneration of GMED, and to assess factors that affect hip abductor strength in patients with unilateral hip OA. Reduction of muscle volume and degeneration of the GMED were evident in the present study, which agrees with findings of previous reports [ 2 – 4 ]. Correlation of hip abductor strength with limping score of HHS, rather than hip pain or walking distance, indicated the importance of hip abductor muscle strength for normal gait in patients with unilateral hip OA.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The purposes of our study were to evaluate the effect of hip abductor muscle strength on hip function, to validate the utility of our CT-based analysis for the quantification of muscle volume and muscle degeneration of GMED, and to assess factors that affect hip abductor strength in patients with unilateral hip OA. Reduction of muscle volume and degeneration of the GMED were evident in the present study, which agrees with findings of previous reports [ 2 – 4 ]. Correlation of hip abductor strength with limping score of HHS, rather than hip pain or walking distance, indicated the importance of hip abductor muscle strength for normal gait in patients with unilateral hip OA.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, dysfunction of the GMED is responsible for unstable hip and postural imbalance of the pelvis during ambulation. A reduction in the volume of the GMED in patients with hip osteoarthritis (OA) is a major reason for limping gait [ 2 – 4 ]. Therefore, quantification of the GMED can provide vital information for obtaining normal gait in patients with hip OA.…”
Section: Introductionmentioning
confidence: 99%
“…This may correlate with BMI through higher muscle mass in men. This is consistent with another study showing equal relative hip muscle distribution in women and men but higher absolute muscle volumes and more muscle relative to BMI in men compared with women [27]. When controlling for other variables like sex and BMI, this study showed no overall differences in muscle damage when using a short versus standard length stem.…”
Section: Discussionsupporting
confidence: 92%
“…Of the remaining 17 pairs, only two of the matched pairs were men. Given previous report of between-sex differences in hip muscle volume, 33 we limited our analysis to the remaining 15 matched pairs of women.…”
Section: Methodsmentioning
confidence: 99%